Performance Evaluation of a Switched-Capacitor Voltage Pump Based Multilevel Inverter (SMART MOVES JOURNAL IJOSCIENCE, 2025)
A multilevel inverter is a power electronic device that is used for high voltage and high power application because of its characteristics of generating a sinusoidal voltage based on several DC voltage levels. They give good quality output resulting with lower harmonic distortion in the output. This topology is designed based on switched-capacitor voltage pump technique and the number of output levels is defined by the number of switched-capacitor cells cascaded. Only one dc voltage source is needed and the problem of voltage balancing across the capacitor is avoided as well. A small input voltage can be used to generate a boosted output voltage, by switching the capacitors in parallel and in series. The basic MLIs are cascaded H-bridge (CHB), neutral point clamped, and flying capacitor inverters. In addition, the inverters inherit various advantages of the original structure, such as a high boost factor of 6, self-balanced capacitor voltages and reduced voltage ripples. Circuit description, operation principle, hybrid PWM modulation and capacitor voltage ripples are analyzed. The capacitor voltages are self-balanced as they are connected in parallel with the input voltage source for several instances in every fundamental cycle.